(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
In order to investigate the pollution with hexavalent chromium (Cr6+) of the groundwater and surface waters around the industrial dump Jugohrom - Jegunovce hydrogeological investigations were carried out, during which during November 2019, 16 samples of groundwater and 3 samples of surface water were taken. Water samples were analyzed at the Institute of Public Health in Skopje, using the method of flame atomic absorption spectrometry (FAAS). The concentration of Cr6+, in most of the analyzed samples of groundwater and surface water exceeds the maximum permissible concentrations of 0.01 mg/l according to the Macedonian and European standards in drinking water. The highest pollution with Cr6+ which is in the range of 0.052 – 132.98 mg/l is registered near the dump in the shallow groundwaters, ie in the aquifers with a free level. Cr6+ contamination ranging from 0.017 to 0.041 mg/l has also been reported in some of the samples at artesian aquifers with sub-artesian level. Two tests were carried out on the surface waters of the Vardar River, before and after the dump. A sevenfold increase in Cr6+ concentration of 0.069 was observed after the dump. Cr6+ content of 725 mg/l was found in the drainage of overflow water in the discharge. Pollution of groundwater and surface water with (Cr6+) is anthropogenic and is a result of the operation of the Metallurgical Plant Jugohrom in the period from 1955 to 1994.